Informal Workers and Collective Action : A Global Perspective - Hawkins, Daniel (Daniel James); Chen, Martha Alter; Schurman, Susan J.; Eaton, Adrienne E. (Book collections on Project MUSE., 2017)
Informal Workers and Collective Action features nine cases of collective action to improve the status and working conditions of informal workers. Adrienne E. Eaton, Susan J. Schurman, and Martha A. Chen set the stage by defining informal work and describing the types of organizations that represent the interests of informal workers and the lessons that may be learned from the examples presented in the book. Cases from a diverse set of countries--Brazil, Cambodia, Colombia, the Dominican Republic, Georgia, Liberia, South Africa, Tunisia, and Uruguay--focus on two broad types of informal workers: "waged" workers, including port workers, beer promoters, hospitality and retail workers, domestic workers, low-skilled public sector workers, and construction workers; and self-employed workers, including street vendors, waste recyclers, and minibus drivers. These cases demonstrate that workers and labor organizations around the world are rediscovering the lessons of early labor organizers on how to aggregate individuals' sense of injustice into forms of collective action that achieve a level of power that can yield important changes in their work and lives. Informal Workers and Collective Action makes a strong argument that informal workers, their organizations, and their campaigns represent the leading edge of the most significant change in the global labor movement in more than a century. Contributors Gocha Aleksandria, Georgian Trade Union Confederation Martha A. Chen, Harvard University and WIEGO Sonia Maria Dias, WIEGO and Federal University of Minas Gerais, Brazil Adrienne E. Eaton, Rutgers, the State University of New Jersey Mary Evans, Rutgers, the State University of New Jersey Janice Fine, Rutgers, the State University of New Jersey Mary Goldsmith, Universidad Autónoma Metropolitana-Xochimilco Daniel Hawkins, National Trade Union School of Colombia Elza Jgerenaia, Labor and Employment Policy Department for the Ministry of Labour, Health and Social Affairs, Republic of GeorgiaStephen J. King, Georgetown University Allison J. Petrozziello, UN Women and the Center for Migration Observation and Social Development Pewee Reed, Ministry of Commerce and Industry, Republic of Liberia Sahra Ryklief, International Federation of Workers' Education Associations Susan J. Schurman, Rutgers, the State University of New Jersey Vera Alice Cardoso Silva, Federal University of Minas Gerais, Brazil Milton Weeks, Devin Corporation.